Vida e Obra do Professor Doutor António Araújo Teixeira - Beatriz Maria Cunha e Sousa (2024)
Introduction: Professor Doctor António Araújo Teixeira was a renowned University Professor and Surgeon. He significantly contributed to the advancement and internalization of Portuguese Surgery. As a Full Professor at FMUP, he influenced many physicians and specialists in the fields of pre and postgraduate education, clinical activity, and health unit management. This dissertation aims to honor and preserve his memory. Materials and Methods: For the preparation of this dissertation, research was conducted in the catalog of the FMUP Library, in the Archives of the University of Porto (UP), in the Archives of São João University Hospital, and in the National Library. In addition to the collected data, interviews were also conducted with former colleagues, collaborators, and family. Results: Professor António Araújo Teixeira, born on November 29, 1931, in the parish of Cedofeita, Porto, was the only child of a prestigious surgeon. Therefore, he showed remarkable academic performance from an early age. He enrolled in the Faculty of Medicine of the University of Porto (FMUP), standing out and being exempted from exams on merit. During his education, he interacted with renowned professionals and cultivated lasting friendships. He began his medical career in 1957, after obtaining an excellent classification in the General Internship. He performed notable activities in the fields of Medicine and Surgery, participated in internships, and began his academic career as a Volunteer Assistant in Topographical Anatomy. He completed an internship in Gastroenterology in Madrid in 1958. In 1962, during an internship in Paris, he attended congresses and specialization courses. Upon returning to Portugal, he continued his clinical and academic activities, standing out as Chief of the Medical Internship and Extraordinary Professor at FMUP. From 1974 onwards, he was appointed Director of Surgery II at São João Hospital, initiating a process of restructuring and modernization, promoting the training of new surgeons, and the internationalization of Portuguese Surgery. After retiring in 2001, as President of the Higher Council of Health Sciences of the Piaget Institute, he led the creation of health schools in Portugal and Portuguese-speaking countries and strengthened international relations. His legacy in surgery and medical education is recognized among his peers, an indelible mark on the Portuguese medical community and in Portuguese-speaking African countries. In addition to his professional career, he valued his family and social life, maintaining a close connection with his wife, children, and grandchildren, and enjoying leisure time and travels around the world. Discussion: Professor António Araújo Teixeira was a prominent figure in Portuguese Surgery, with international recognition. His pursuit of excellence and innovation in clinical practice, combined with his commitment to medical education, marked his career. His influence, both professional and humanistic, left a legacy spanning several generations. Conclusion: The legacy of Professor António Araújo Teixeira in Portuguese Surgery is undeniable. His tireless dedication raised the national standard, influencing generations of surgeons. His name will be remembered as one of the most prominent figures in the history of Surgery in Portugal, leaving a transgenerational impact.